1,2,3-Triazoles as leaving groups: SNAr reactions of 2,6-bistriazolylpurines with O- and C-nucleophiles - Cīrule, Dace; Novosjolova, Irina; Bizdēna, Ērika; Turks, Māris (Beilstein Journal of Organic Chemistry, 2021)
A new approach was designed for the synthesis of C6-substituted 2-triazolylpurine derivatives. A series of substituted products was obtained in SNAr reactions between 2,6-bistriazolylpurine derivatives and O- and C-nucleophiles under mild conditions. The products were isolated in yields up to 87%. The developed C–O and C–C bond forming reactions clearly show the ability of the 1,2,3-triazolyl ring at the C6 position of purine to act as leaving group.
Keywords: 2,6-bistriazolyl purines; nucleophilic aromatic substitution; purine nucleosides; triazoles

(untitled) - Dinesh, S.; Shikha, G.; Bhavana, G.; Nidhi, S.; Dileep, S. (J. Pharm. Sci. Innovation, 2012)

(untitled) - Parker, W. B. (Chem. Rev., 2009)

(untitled) - Shelton, J.; Lu, X.; Hollenbaugh, J. A.; Cho, J. H.; Amblard, F.; Schinazi, R. F. (Chem. Rev., 2016)

(untitled) - Seley-Radtke, K. L.; Yates, M. K. (Antiviral Res., 2018)

(untitled) - Yates, M. K.; Seley-Radtke, K. L. (Antiviral Res., 2019)

SOS Knowledge Updates 2020/1 - Liang, Y.; Wen, Z.; Cabrera, M.; Howlader, A. H.; Wnuk, S. F. (Purines (Update 2020), 2020)

(untitled) - Véliz, E. A.; Beal, P. A. (J. Org. Chem., 2001)

(untitled) - Lakshman, M. K.; Frank, J. (Org. Biomol. Chem., 2009)

(untitled) - Manvar, A.; Shah, A. (Tetrahedron, 2013)

(untitled) - Manvar, A.; Shah, A. (Tetrahedron, 2013)

(untitled) - Kovaļovs, A.; Novosjolova, I.; Bizdēna, Ē.; Bižāne, I.; Skardziute, L.; Kazlauskas, K.; Jursenas, S.; Turks, M. (Tetrahedron Lett., 2013)

(untitled) - Aleksandrova, E. V. (Pharm. Chem. J., 2003)

(untitled) - Aleksandrova, E. V.; Kochergin, P. M. (Pharm. Chem. J., 2013)

(untitled) - Novosjolova, I.; Bizdēna, Ē.; Turks, M. (Tetrahedron Lett., 2013)

(untitled) - Gurram, V.; Pottabathini, N.; Garlapati, R.; Chaudhary, A. B.; Patro, B.; Lakshman, M. K. (Chem. – Asian J., 2012)

(untitled) - Lakshman, M. K.; Gunda, P.; Pradhan, P. (J. Org. Chem., 2005)

(untitled) - Havelková, M.; Hocek, M.; Česnek, M.; Dvořák, D. (Synlett, 1999)

(untitled) - Havelková, M.; Dvořak, D.; Hocek, M. (Synthesis, 2001)

(untitled) - Hocek, M.; Masojídková, M.; Holý, A. (Collect. Czech. Chem. Commun., 1997)

(untitled) - Hasník, Z.; Pohl, R.; Hocek, M. (Synthesis, 2009)

(untitled) - Guo, H.-M.; Xin, P.-Y.; Niu, H.-Y.; Wang, D.-C.; Jiang, Y.; Qu, G.-R. (Green Chem., 2010)

(untitled) - Pathak, A. K.; Pathak, V.; Seitz, L. E.; Suling, W. J.; Reynolds, R. C. (Bioorg. Med. Chem., 2013)

(untitled) - McGuigan, C.; Madela, K.; Aljarah, M.; Gilles, A.; Battina, S. K.; Ramamurty, C. V. S.; Srinivas Rao, C.; Vernachio, J.; Hutchins, J.; Hall, A.; Kolykhalov, A.; Henson, G.; et al. (Bioorg. Med. Chem. Lett., 2011)

(untitled) - Vijay Kumar, D.; Hoarau, C.; Bursavich, M.; Slattum, P.; Gerrish, D.; Yager, K.; Saunders, M.; Shenderovich, M.; Roth, B. L.; McKinnon, R.; Chan, A.; Cimbora, D. M.; et al. (Bioorg. Med. Chem. Lett., 2012)

(untitled) - Hulpia, F.; Balzarini, J.; Schols, D.; Andrei, G.; Snoeck, R.; Van Calenbergh, S. (Bioorg. Med. Chem. Lett., 2016)

(untitled) - Bonnac, L. F.; Dreis, C. D.; Geraghty, R. J. (Bioorg. Med. Chem. Lett., 2020)

(untitled) - Besada, P.; Costas, T.; Teijeira, M.; Terán, C. (Eur. J. Med. Chem., 2010)

(untitled) - Daumar, P.; Zeglis, B. M.; Ramos, N.; Divilov, V.; Sevak, K. K.; Pillarsetty, N.; Lewis, J. S. (Eur. J. Med. Chem., 2014)

(untitled) - Bae, S.; Lakshman, M. K. (J. Am. Chem. Soc., 2007)

(untitled) - Kokatla, H. P.; Lakshman, M. K. (Org. Lett., 2010)

(untitled) - Basava, V.; Yang, L.; Pradhan, P.; Lakshman, M. K. (Org. Biomol. Chem., 2016)

(untitled) - Bae, S.; Lakshman, M. K. (J. Org. Chem., 2008)

(untitled) - Zhong, M.; Nowak, I.; Robins, M. J. (Org. Lett., 2005)

(untitled) - Zhong, M.; Nowak, I.; Robins, M. J. (J. Org. Chem., 2006)

(untitled) - Linn, J. A.; McLean, E. W.; Kelley, J. L. (J. Chem. Soc., Chem. Commun., 1994)

(untitled) - Lakshman, M. K.; Ngassa, F. N.; Keeler, J. C.; Dinh, Y. Q. V.; Hilmer, J. H.; Russon, L. M. (Org. Lett., 2000)

(untitled) - Schirrmacher, R.; Wängler, B.; Schirrmacher, E.; August, T.; Rösch, F. (Synthesis, 2002)

(untitled) - Schirrmacher, R.; Mühlhausen, U.; Wängler, B.; Schirrmacher, E.; Reinhard, J.; Nagel, G.; Kaina, B.; Piel, M.; Wießler, M.; Rösch, F. (Tetrahedron Lett., 2002)

(untitled) - Miles, R. W.; Samano, V.; Robins, M. J. (J. Am. Chem. Soc., 1995)

(untitled) - Clivio, P.; Fourrey, J.-L.; Favre, A. (J. Chem. Soc., Perkin Trans. 1, 1993)

(untitled) - Caner, J.; Vilarrasa, J. (J. Org. Chem., 2010)

(untitled) - Geigle, S. N.; Wyss, L. A.; Sturla, S. J.; Gillingham, D. G. (Chem. Sci., 2017)

(untitled) - Vincent, S. P.; Mioskowski, C.; Lebean, L. (Nucleosides Nucleotides, 1999)

(untitled) - Woo, J.; Sigurdsson, S. T.; Hopkins, P. B. (J. Am. Chem. Soc., 1993)

(untitled) - Wilds, C. J.; Booth, J. D.; Noronha, A. M. (Tetrahedron Lett., 2006)

(untitled) - Wang, L.; Spratt, T. E.; Liu, X.-K.; Hecht, S. S.; Pegg, A. E.; Peterson, L. A. (Chem. Res. Toxicol., 1997)

(untitled) - Giordano, C.; Pedone, F.; Fattibene, P.; Cellai, L. (Nucleosides, Nucleotides Nucleic Acids, 2000)

(untitled) - Cooper, M. D.; Hodge, R. P.; Tamura, P. J.; Wilkinson, A. S.; Harris, C. M.; Harris, T. M. (Tetrahedron Lett., 2000)

(untitled) - Harwood, E. A.; Hopkins, P. B.; Sigurdsson, S. T. (J. Org. Chem., 2000)

(untitled) - De Napoli, L.; Di Fabio, G.; Messere, A.; Montesarchio, D.; Piccialli, G.; Varra, M. (J. Chem. Soc., Perkin Trans. 1, 1999)

(untitled) - Zhang, Y.; Wang, L.; Zhang, Q.; Zhu, G.; Zhang, Z.; Zhou, X.; Chen, Y.; Lu, T.; Tang, W. (J. Chem. Inf. Model., 2017)

(untitled) - Hamamichi, N.; Miyasaka, T. (J. Org. Chem., 1994)

(untitled) - Hamamichi, N.; Miyasaka, T. (Tetrahedron Lett., 1985)

(untitled) - Hamamichi, N.; Miyasaka, T. (J. Heterocycl. Chem., 1990)

(untitled) - Hamamichi, N. (Tetrahedron Lett., 1991)

(untitled) - Timoshchuk, V. (Nucleosides, Nucleotides Nucleic Acids, 2005)

(untitled) - Amblard, F.; Cho, J. H.; Schinazi, R. F. (Chem. Rev., 2009)

(untitled) - Novosjolova, I.; Bizdēna, Ē.; Turks, M. (Eur. J. Org. Chem., 2015)

(untitled) - Cosyn, L.; Palaniappan, K. K.; Kim, S.-K.; Duong, H. T.; Gao, Z.-G.; Jacobson, K. A.; Van Calenbergh, S. (J. Med. Chem., 2006)

(untitled) - Gupte, A.; Boshoff, H. I.; Wilson, D. J.; Neres, J.; Labello, N. P.; Somu, R. V.; Xing, C.; Barry, C. E.; Aldrich, C. C. (J. Med. Chem., 2008)

(untitled) - Lakshman, M. K.; Kumar, A.; Balachandran, R.; Day, B. W.; Andrei, G.; Snoeck, R.; Balzarini, J. (J. Org. Chem., 2012)

(untitled) - Cīrule, D.; Ozols, K.; Platnieks, O.; Bizdēna, Ē.; Māliņa, I.; Turks, M. (Tetrahedron, 2016)

(untitled) - Novosjolova, I.; Bizdēna, Ē.; Turks, M. (Phosphorus, Sulfur Silicon Relat. Elem., 2015)

(untitled) - Palle, V. P.; Elzein, E. O.; Gothe, S. A.; Li, Z.; Gao, Z.; Meyer, S.; Blackburn, B.; Zablocki, J. A. (Bioorg. Med. Chem. Lett., 2002)

(untitled) - Gao, Z.; Li, Z.; Baker, S. P.; Lasley, R. D.; Meyer, S.; Elzein, E.; Palle, V.; Zablocki, J.; Blackburn, B.; Belardinelli, L. (J. Pharmacol. Exp. Ther., 2001)

(untitled) - Elzein, E.; Kalla, R.; Li, X.; Perry, T.; Marquart, T.; Micklatcher, M.; Li, Y.; Wu, Y.; Zeng, D.; Zablocki, J. (Bioorg. Med. Chem. Lett., 2007)

(untitled) - Šišuļins, A.; Bucevičius, J.; Tseng, Y.-T.; Novosjolova, I.; Traskovskis, K.; Bizdēna, Ē.; Chang, H.-T.; Tumkevičius, S.; Turks, M. (Beilstein J. Org. Chem., 2019)

(untitled) - Zayas, J.; Annoual, M.; Das, J. K.; Felty, Q.; Gonzalez, W. G.; Miksovska, J.; Sharifai, N.; Chiba, A.; Wnuk, S. F. (Bioconjugate Chem., 2015)

(untitled) - Dyrager, C.; Börjesson, K.; Dinér, P.; Elf, A.; Albinsson, B.; Wilhelmsson, L. M.; Grøtli, M. (Eur. J. Org. Chem., 2009)

(untitled) - Jovaisaite, J.; Cīrule, D.; Jeminejs, A.; Novosjolova, I.; Turks, M.; Baronas, P.; Komskis, R.; Tumkevicius, S.; Jonusauskas, G.; Jursenas, S. (Phys. Chem. Chem. Phys., 2020)

Heterocyclic Chemistry at a Glance - Joule, J. A.; Mills, K. (Purines, 2012)

The Chemistry of Heterocycles: Structure, Reactions, Synthesis, and Applications - Eicher, T.; Hauptmann, S.; Speicher, A. (Wiley-VCH, 2012)

(untitled) - Gunda, P.; Russon, L. M.; Lakshman, M. K. (Angew. Chem., Int. Ed., 2004)

(untitled) - Lagisetty, P.; Russon, L. M.; Lakshman, M. K. (Angew. Chem., Int. Ed., 2006)

(untitled) - Thomson, P. F.; Lagisetty, P.; Balzarini, J.; De Clercq, E.; Lakshman, M. K. (Adv. Synth. Catal., 2010)

Palladium-Catalyzed Modification of Nucleosides, Nucleotides and Oligonucleotides - Liang, Y.; Wnuk, S. F. (C-H Bond Functionalization Strategies for Modification of Nucleosides, 2018)

(untitled) - Kriķis, K.-Ē.; Novosjolova, I.; Mishnev, A.; Turks, M. (Beilstein J. Org. Chem., 2021)

(untitled) - Kapilinskis, Z.; Novosjolova, I.; Bizdēna, Ē.; Turks, M. (Chem. Heterocycl. Compd., 2021)

(untitled) - Qu, G.-R.; Mao, Z.-J.; Niu, H.-Y.; Wang, D.-C.; Xia, C.; Guo, H.-M. (Org. Lett., 2009)

(untitled) - Guo, H.-M.; Zhang, Y.; Niu, H.-Y.; Wang, D.-C.; Chu, Z.-L.; Qu, G.-R. (Org. Biomol. Chem., 2011)

(untitled) - Bordwell, F. G. (Acc. Chem. Res., 1988)

Structure Determination of Organic Compounds - Pretsch, E.; Bühlmann, P.; Badertscher, M. (Springer, 2009)

(untitled) - Hamamichi, N.; Miyasaka, T. (J. Heterocycl. Chem., 1991)

(untitled) - Odijk, W. M.; Koomen, G. J. (Tetrahedron, 1985)

(untitled) - Zaki, M. E. A.; Proença, M. F.; Booth, B. L. (J. Org. Chem., 2003)